BDNF DNA methylation changes as a biomarker of psychiatric disorders: literature review and open access database analysis. Issue 1 (December 2016) - Zheleznyakova, Galina; Cao, Hao; Schiöth, Helgi
Abstract Brain-derived neurotrophic factor (BDNF) plays an important role in nervous system development and function and it is well established that BDNF is involved in the pathogenesis of a wide range of psychiatric disorders. Recently, numerous studies have associated the DNA methylation level ofBDNF promoters with certain psychiatric phenotypes. In this review, we summarize data from current literature as well as from our own analysis with respect to the correlation ofBDNF methylation changes with psychiatric disorders and address questions about whether DNA methylation related to theBDNF can be useful as biomarker for specific neuropsychiatric disorders.